Wife’s Right to Reject Polygamy: Islamic Family Law, Indonesian Positive Law, and the Maslahah Mursalah Perspective - Annisaa, Winona Nur (Unisia, 2025)
This article examines wife’s right to reject polygamy in the perspective of maslahah mursalah within the context of contemporary Islamic family law and Indonesian positive law. The study aims to clarify whether a wife’s refusal of polygamy can be normatively recognized as a legitimate legal and ethical stance that safeguards justice and family welfare. Using a qualitative, normative legal methodology based on document and library research, the analysis draws on legislation, Qur’anic and Hadith texts, classical and contemporary fiqh, court decisions, and scholarly works on polygamy and maslahah mursalah. The findings show that polygamy in Islam is legally permitted but strictly conditioned on the husband’s ability to uphold justice in material and emotional terms, while Indonesian law adopts monogamy as the main principle and allows polygamy only as a limited exception under stringent procedural and substantive requirements, including court permission and the wife’s consent. Empirical indications, such as increasing divorce cases related to polygamy, and case law where courts reject polygamy petitions that fail to meet legal standards, demonstrate that polygamy often generates harm rather than welfare for wives and families. Through the lens of maslahah mursalah, the wife’s right to reject polygamy is interpreted as a legitimate effort to prevent psychological, social, and economic harm and to preserve the integrity and well-being of the family. The article concludes that recognizing this right is consistent with the objectives of Islamic law and strengthens the protective function of Indonesian family law, offering a doctrinal basis for more justice-oriented interpretations of polygamy regulations.